THE METHOD OF MATHEMATICAL MODELING OF SWITCH ECLECTIC DRIVE - Buryak, S. Yu. (Science and Transport Progress, 2010)
The method of mathematical modeling of switch eclectic drive in the system MATLAB + Simulink is presented.